AB0937 IDENTIFYING THE PRIMARY OUTCOME MEASURE AND PROTOCOL COMPONENTS FOR A PROSPECTIVE FEASIBILITY STUDY OF CORTICOSTEROID REGIMENS FOR CHILDREN AND YOUNG PEOPLE WITH JUVENILE IDIOPATHIC ARTHRITIS USING CONSENSUS METHODS WITH YOUNG PEOPLE, FAMILIES AND PROFESSIONALS. (June 2019) - Stones, Simon; Bagley, Heather; Jones, Ashley; Mcerlane, Flora; Moitt, Tracy; Nkhoma, Gloria; Sherratt, Frances; Young, Bridget; Beresford, Michael; Baildam, Eileen; ,
Abstract : Background: Juvenile idiopathic arthritis (JIA) is an umbrella term for seven relapsing-remitting inflammatory conditions in children and young people (CYP). Early, intensive treatment can prevent long-term damage; however, established drugs exhibit a delayed response, prompting the need for rapid-onset treatment in the form of corticosteroids. Given a lack of consensus as to which corticosteroid induction regimen should be used for CYP with JIA, a feasibility trial of different regimens is needed. Objectives: The aim was to achieve consensus among CYP, families, and healthcare professionals (HCPs) about the primary outcome measures and protocol components to include in a prospective feasibility study. Methods: A modified Nominal Group Technique was used to achieve consensus on the most appropriate primary outcome measure to be included in a prospective feasibility study, in addition to other protocol components such as inclusion/exclusion criteria. Fifteen participants participated in the process, including a combination of CYP with JIA, families (n=9) and HCPs (n=6). Results: In the first vote, participants agreed that 'Juvenile Arthritis Disease Activity Score (JADAS)' and 'Physician Global Assessment Score' were most meaningful. During sub-group discussions, the need for a composite score which captured the voice of CYP and families was emphasised. In the second vote, 'JADAS' and the 'JIA Core Set' were identified as the most important. Further discussions led to the results of the third vote, agreeing 'JADAS' as the primary outcome measure of choice being measured at 6 weeks after commencement of treatment. The majority of HCPs, CYP and families voted for all JIA sub-types to be included in a prospective feasibility study, with some queries about the inclusion of systemic JIA given its unique presentation. Participants also identified the need for more frequent data collection time points to capture the rapid onset of corticosteroid action, while CYP and families opted for accessible mechanisms for participation, such as digital follow-up strategies. Conclusion: It is feasible to include CYP, families and HCPs in synthesising complex concepts to agree by consensus the design components of clinical research. The primary outcome measure for inclusion in a prospective feasibility study of corticosteroid regimens in CYP with JIA was co-prioritised, with CYP and families taking a leading role in the ultimate selection of an appropriate outcome measure and other study protocol components. Using consensus methods with CYP, families and HCPs is a systematic and rigorous way in which to select outcome measures that are both meaningful and relevant to everyone involved in the care and treatment of CYP with JIA. References: [1] Sherratt F, et al. Family perspectives on the feasibility of a corticosteroid induction regimen trial in juvenile idiopathic arthritis. In: International Clinical Trials Methodology Conference: 2017; Liverpool, UK: Trials; 2017 Acknowledgement: This consensus meeting was funded as part of the SIRJIA study, funded by the NIHR Health Technology Assessment Programme (14/167/01). The funders did not have a role in the design, collection, analysis, or interpretation of the data Disclosure of Interests: Simon Stones Consultant for: SS has provided consultancy services to Envision Pharma Group, though this is not related to the contents of this abstract., Speakers bureau: SS has undertaken speaking engagements for Actelion, eyeforpharma, Four Health, Janssen and Roche, though these are not related to the contents of this abstract., Heather Bagley: None declared, Ashley Jones: None declared, Flora McErlane: None declared, Tracy Moitt: None declared, Gloria Nkhoma: None declared, Frances Sherratt: None declared, Bridget Young: None declared, Michael Beresford: None declared, Eileen Baildam Consultant for: EB has received one paid consultancy for Pfizer in the last 12 months, but this was not related to this study.